Analysis of the Number of Euploid Embryos in Preimplantation Genetic Testing Cycles With Early-Follicular Phase Long-Acting Gonadotropin-Releasing Hormone Agonist Long Protocol - Li, Gang; Wu, Yifang; Niu, Wenbin; Xu, Jiawei; Hu, Linli; Shi, Hao; Sun, Yingpu (Frontiers in Endocrinology, 2020)
Studies have shown that early-follicular phase long-acting gonadotropin-releasing hormone (GnRH) agonist long protocol (EFLL), a popular controlled ovarian hyperstimulation protocol widely used in China, leads to higher rates of implantation and clinical pregnancy, as well as lower rates of spontaneous abortion and ectopic pregnancy in patients undergoing in vitro fertilization (IVF) treatment. However, the impact of EFLL on euploid embryos and its underlying mechanisms remain unclear. To address these gaps of knowledge, we conducted a retrospective comparative study of 310 preimplantation genetic testing (PGT) cycles with a total of 1541 embryos using the EFLL protocol or mid-luteal long-acting GnRH agonist short protocol (MLSL). Patients were matched by PGT subtype (aneuploidies (PGT-A) vs. preimplantation genetic testing for chromosomal structural rearrangements (PGT-SR), age (±2 years) and body mass index (BMI) (±1 kg/m2). For PGT-A, there was no significant difference in the number of euploid embryos (1.80±1.47 for EFLL vs. 1.84±2.03 for MLSL, p>0.05) or the rate of euploidy (44.6% vs.36.9%, p>0.05). For PGT-SR, the number of euploid embryos in the EFLL group was significantly higher than that in the MLSL group (1.76±1.54 vs. 1.21±1.24, p<0.05). A higher euploidy rate was also observed with the EFLL protocol compared with that obtained in MLSL (31.9% vs. 25.7%), although the difference was not statistically significant (p>0.05). Compared with the MLSL protocol, more euploid embryos were achieved when using the EFLL protocol in PGT-SR, demonstrating the value in PGT-SR. To the best of our knowledge, this study is the first one to compare embryonic outcomes between EFLL and MLSL, providing key insights into the clinical application of EFLL in PGT cycles. In the light of the limited sample size of our study, we recommend that these questions be explored using a larger prospective study.